2015
DOI: 10.5433/1679-0359.2015v36n6p3897
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics in vitro of ruminal fermentation of cocoa husks subjected to alkali and heat treatment

Abstract: The objective was to evaluate the parameters of kinetics of ruminal fermentation of cocoa husks (CH) treated with alkali and thermal agents, using the semi-automated in vitro gas production technique. Cocoa husks samples were subjected to alkali and thermal methods (effect of time of exposure) treatment, as follows: control; alkaline treatment with calcium hydroxide ((Ca(OH) 2 ) and calcium oxide (CaO), both doses of 15.0; 30.0 and 45.0 g kg -1 of CH; heat treatment in an autoclave at a pressure of 1.23 kg cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…As FC have a slower rate of degradation, as can be seen in Table 3, the larger volume of gases from the FC would occur in later periods. This behavior is presented by Almeida et al (2015) with incubation of cocoa husks that observed that the gases from the degradation of the NFC reached asymptote in period near the 12 hours of incubation while the volume of the gases from the degradation of the FC continued increasing beyond the 120 hours. Similarly, Benedeti et al (2018) observed that the asymptote of the gases from the starch fermentation was reached until 12 hours while corn continued its production beyond 48 hours.…”
Section: Resultsmentioning
confidence: 91%
“…As FC have a slower rate of degradation, as can be seen in Table 3, the larger volume of gases from the FC would occur in later periods. This behavior is presented by Almeida et al (2015) with incubation of cocoa husks that observed that the gases from the degradation of the NFC reached asymptote in period near the 12 hours of incubation while the volume of the gases from the degradation of the FC continued increasing beyond the 120 hours. Similarly, Benedeti et al (2018) observed that the asymptote of the gases from the starch fermentation was reached until 12 hours while corn continued its production beyond 48 hours.…”
Section: Resultsmentioning
confidence: 91%
“…O estudo da cinética de fermentação ruminal permite conhecer o valor nutricional de forragens (alMeida et al, 2015), possuindo alta correlação entro o consumo e a digestibilidade in vivo (OrSkOV, 2002). Além de que, a técnica de produção de gás in vitro simula o ambiente ruminal (theOdOrOu, 1994), permitindo estudar os parâmetros cinéticos das fracções que constituem os alimentos, refletindo a velocidade à qual os componentes são fermentados pelos microrganismos ruminais e a extensão da fermentação (CaBral et al, 2002).…”
Section: Introductionunclassified